2006
DOI: 10.1063/1.2392818
|View full text |Cite
|
Sign up to set email alerts
|

Ground state monoclinic (Mb) phase in (110)c BiFeO3 epitaxial thin films

Abstract: The lattice structure of (110)-oriented BiFeO3 epitaxial thin layers has been identified by synchrotron x-ray diffraction. By using (221) and (221¯) peaks in the (HHL) zone, a ground state monoclinic Mb phase has been observed with lattice parameters of (β;am∕√2andcm)=(89.35°;3.985and3.888Å). These results demonstrate a change in phase stability from rhombohedral in bulk single crystals, to monoclinic in epitaxial thin films with two domain states whose polarization is slightly tilted away from [110] towards [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
28
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 21 publications
(19 reference statements)
1
28
0
Order By: Relevance
“…Domain formation is established as a mechanism for accommodating the stress. We propose that the monoclinic domains observed here in LaCoO 3 materials may also be of importance for stress accommodation in other rhombohedral perovskites such as magnetoresistant Sr doped LaMnO 3 [31,32] and multiferroic BiFeO 3 [33,34] . Careful choice of chemical substitution in the film and/or substrate might give a designed lattice mismatch between film and substrate in order to tailor a specific ferroic domain pattern.…”
mentioning
confidence: 91%
“…Domain formation is established as a mechanism for accommodating the stress. We propose that the monoclinic domains observed here in LaCoO 3 materials may also be of importance for stress accommodation in other rhombohedral perovskites such as magnetoresistant Sr doped LaMnO 3 [31,32] and multiferroic BiFeO 3 [33,34] . Careful choice of chemical substitution in the film and/or substrate might give a designed lattice mismatch between film and substrate in order to tailor a specific ferroic domain pattern.…”
mentioning
confidence: 91%
“…4b). The similar monoclinic structure model is also introduced in this orientation [19] ( Fig. 4c and d).…”
mentioning
confidence: 98%
“…Since the crystal structure and/or lattice parameters of the substrates are different from those of BFO material, BFO thin films are expected to be under lattice stress/strain, which is closely related to increased polarization values as well as other physical properties in epitaxial BFO thin films. Thus, considerable experimental and theoretical efforts have been devoted to understand the lattice stress/strain effects on epitaxial BFO films that present lattice distortions found in rhombohedral unit cell of bulk BFO6101112 and also different BFO crystal unit cell structures1314151617181920. Recently, it was suggested that, while BFO thin films are likely to possess tetragonal and/or monoclinic structures (denoted as M C and M A ) under compressive stress, they rather grow as orthorhombic and/or monoclinic structures of a different type (M B ) under tensile stress21.…”
mentioning
confidence: 99%
“…However, the precise crystal models that can explain experimentally found highly stressed BFO are rather unclear as has been pointed out very recently2223. Most of the experimental reports dealing with strain effects on epitaxially grown BFO films are making discussions based on lattice parameter changes and/or unit cell distortion61011121314151617181920. On the other hand, it is worth noting that when those lattice parameter changes and/or unit cell distortions occur in epitaxially grown BFO films, locations of basis atoms in the unit cell change as well, which lead to corresponding alteration in its reciprocal space in terms of locations, symmetries, and shapes in Bragg’s reflections.…”
mentioning
confidence: 99%